Testing Claims of Crime-Related Amnesia - Jelicic, Marko (Frontiers in Psychiatry, 2018)
Many violent offenders report amnesia for their crime. Although this type of memory loss is possible, there are reasons to assume that many claims of crime-related amnesia are feigned. This article describes ways to evaluate the genuineness of crime-related amnesia. A recent case is described in which several of these strategies yielded evidence for feigned crime-related amnesia.